Improving care for thalassemia patients in line with best practice standards at a tertiary referral cancer care center. Issue 2 (12th June 2022) - Bongay, Leilani; Kynoch, Kathryn
ABSTRACT: Background: Beta-thalassemia major is a chronic hematological disorder that requires life-long management. This project aimed to improve thalassemia patients' care through the implementation of best practice standards at a tertiary referral cancer care center. Methods: The current project utilized a clinical audit design. A pre and post-implementation audit was carried out following best practice standards for patients with thalassemia. Chart review of nine thalassemia patients was undertaken pre and post-implementation of staff education, local clinical guidelines, and an annual care plan to manage thalassemia to determine adherence to best practice standards. Data were collected between June 2019 and June 2020 at a specialist outpatient and day treatment unit located in inner Brisbane, Australia. Results: The pre-implementation audit results showed low compliance to the audit criteria, with the exception of nursing staff education. Following the implementation of strategies to align current care with evidence-based recommendations, the post-implementation audit showed improvement across all areas. Overall, implementation strategies were successful in improving patient care for thalassemia patients by 100%. Staff thalassemia education increased from 45 to 92%. Conclusion: Implementing an individualized treatment plan and thalassemia-specific nursing documentation as well as developing local clinical guidelines and providing targeted nurse education were effective strategies to improve care for thalassemia patients in line with best practice standards.